RESPON MODEL HBV DAN MODEL TANGKI TERHADAP ESTIMASI DEBIT ALIRAN DI DAS BOGOWONTO, JAWA TENGAH - Andini, Fitri Yusti; Dasanto, Bambang Dwi; Santikayasa, I Putu (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2023)
The scarcity of discharge data compared to rainfall data have driven the development of the rainfall-runoff model, such as the HBV and Tank models. This research aims to apply the rainfall-runoff model in the Bogowonto watershed and to assess the model outputs. The research consisted of two main stages: 1) model calibration and validation; 2) model evaluation which assesses the model performance based on the Nash-Sutcliffe Efficiency (NSE) index and the coefficient of determination (R2). The results showed that the pattern of the simulation discharge was in accordance with the observed discharge pattern; indicating performance of both models was good (NSE > 0.7 and R2 > 0.65). However, the performance of both models in the daily simulation, particularly at the beginning of the simulation period, is still not satisfactory as the simulated discharge does not match the observed discharge. In the next simulation period, the discharge of the model results were in accordance with the observed discharge; this means the performance of the model was better. In the monthly simulation, the performance of both models is not yet satisfactory during the wet season, but it is good during the dry season. Based on the results of the daily and monthly simulations, both models demonstrate good performance under low precipitation conditions, but their performance declines under high precipitation conditionsKeywords: Bogowonto watershed, HBV, rainfall-runoff model, simulation, tank